Design of a Greenhouse Room Temperature and Humidity Control System Using a DHT 22 Sensor - Husnul Mubarak; Muhammad Rizal; Iqbal Iqbal; Abdul Waris; Muhammad Tahir Sapsal; Imam Suelfikhar (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2022)
Temperature and humidity conditions in plant growth are one of the important factors. Instability of temperature and humidity is often a problem that makes plants grow not optimally. The use of a green house is one way to artificially maintain temperature and humidity, but it still experiences several problems due to unstable weather conditions that affect conditions in the green house space. The control system uses temperature and humidity sensors (DHT 22) to measure the conditions in the green house space which can be used to maintain the stability of temperature and humidity in the green house. This control system will be connected to a water pump connected to a misting device where the water vapor produced by the misting is expected to be able to maintain the humidity in the green house room, and the control device will be connected to a fan which is expected to be able to maintain the temperature conditions in the green house room. The measurement data of the control system tool using the DHT 22 sensor will be compared with the hygrometer measurement data for the calibration process. Testing the function of the control device is carried out by looking at the response of the fan and pump to the setting point on the DHT 22 sensor reading. This control system is very important to apply because it can become the basis for developing greenhouses in the future, and as a basis for developing several control systems related to plant growth. The calibration results for the DHT 22 sensor and hygrometer readings obtained an error value of 0.27 °C for the temperature sensor and 1.23% for the humidity sensor. This value indicates that the sensor reading error is within the temperature sensor tolerance standard, which is ±0.5 °C and the humidity sensor tolerance is ±5%. For the results of testing the response of the pump and fan to the setting point, it shows that the two tools work well. So that it can be concluded that the design of the tool can function properly in controlling the green house space to maintain temperature and humidity stability.